ENERGY RECOVERY FROM GAS-CHEMICAL WASTE TO REDUCE ENVIRONMENTAL IMPACT (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This research explores the possibilities of energy recovery and environmental impact reduction through pyrolysis processing of gas-chemical industry waste. The study focuses on obtaining alternative fuels from waste using modern thermochemical technologies and reducing greenhouse gas emissions.